2011
DOI: 10.1103/physrevc.84.054308
|View full text |Cite
|
Sign up to set email alerts
|

Candidate for the 2+excited Hoyle state atEx10 MeV in12<

Abstract: Inelastic scattering from12 C has been measured at the extremely forward angles including 0• using 386 MeV α particles to study the α-cluster states around Ex ∼ 10 MeV, especially the 2 + state predicted by the α-cluster model. We have analyzed the (α,α ′ ) cross-section data using both the peak-fitting and the multipole decomposition techniques. A 2 + state at Ex = 9.84 ± 0.06 MeV with a width of 1.01 ± 0.15 MeV is found to be submerged in the broad 0 + state at Ex = 9.93 ± 0.03 MeV with a width of 2.71 ± 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
201
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(232 citation statements)
references
References 30 publications
28
201
3
Order By: Relevance
“…(B1) can be comparable or even larger than the last two terms of Eq. (12). We conclude that, if the cluster nucleus has the rotational or vibrational ground band with an enhanced E2 transition, the internal excitation of the cluster from 0 + to 2 + can have a large contribution to IS dipole excitation.…”
Section: Appendix B: Derivation Of Isoscalar Dipole Matrix Elementmentioning
confidence: 98%
See 4 more Smart Citations
“…(B1) can be comparable or even larger than the last two terms of Eq. (12). We conclude that, if the cluster nucleus has the rotational or vibrational ground band with an enhanced E2 transition, the internal excitation of the cluster from 0 + to 2 + can have a large contribution to IS dipole excitation.…”
Section: Appendix B: Derivation Of Isoscalar Dipole Matrix Elementmentioning
confidence: 98%
“…In Ref. [31], taking 12 C and 16 O as examples, it was shown that the IS monopole transition matrix from the ground state to the nodal excited cluster states is large.…”
Section: Wave Functions Of Ground State and Nodal And Angular Excitedmentioning
confidence: 99%
See 3 more Smart Citations